APLIKASI ZERO WASTE DALAM LINGKUNGAN MASYARAKAT DESA TUMPUKRENTENG DENGAN PENDEKATAN ASET BASE COMMUNITY DEVELOPMENT THEORY - Alisah, Evawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Constructing dreams together with discovering a unique and communally defined design in a particular place destination in overcoming the problem of waste is an achievement that should be appreciated. Go to Zero Waste must indeed be raised in all circles so that the predicate of producing plastic waste is no longer attached to Indonesia.Inorganic waste from family level activities, whose sustainability is maintained because of adat: is managed together with a simple organization and the amount is limited eventually if accumulated will become a mountain of problems that are resolved, even into results that can be utilized. The solution model can be applied elsewhere in order to solve the problem of garbage from the family level during the celebration. RT 13 RW 03 neighborhood of Tumpukrenteng Village, Turen District, Malang Regency has proven that it can mobilize assets for small things, such as garbage so that it becomes a blessing.